ТҮРІК ТІЛІНДЕГІ КӨПМАҒЫНАЛЫ ЭТИКЕТ ТІЛДІК БІРЛІКТЕР - Шадкам, З. (Journal of Oriental Studies, 2016)
In the article it is considered the forms and usage of multisemantic etiquette Linguistical units with their examples.